Textural and quality characteristics of doughnuts produced from wheat and date flours as sugar substitute (Agriculture, Food, and Natural Resources Journal, 2025)
Snacks are important short meals, and sugar is a key component in most snack and food products. However, many health challenges have been linked to the consumption of sugar. This study aimed to evaluate the effect of date fruit flour as a sugar substitute at varying proportions on the textural and quality characteristics of doughnuts made from wheat flour. Doughnuts were produced from blends of wheat and date fruit flour in the following proportions: 95:5 (W95D5), 90:10 (W9s0D10), 85:15 (W85D15), 80:20 (W80D20), and 100% wheat flour (W100) as the control. The flour blends were kneaded, shaped, and deep-fried in hot vegetable oil at a constant temperature of 130°C for 10 min.  Textural and colour parameters of the doughnuts were determined using a Model CT310K Texture Analyzer and a Chroma Meter CR-410, respectively. The functional properties of the wheat-date flour blends (WDF) were evaluated using standard procedures. The results showed a significant difference (p < 0.05) in the textural properties of the doughnuts. The color values L* (33.93 - 46.63), a* (2.51 - 6.45), and b* (3.11 - 11.59) revealed noticeable changes with increasing substitution levels of date fruit flour.  There was no significant difference (p > 0.05) in the overall acceptability of the control sample (W100) compared to the W95:D5 and W90:D10 doughnut samples. These findings revealed that date fruit, as a natural sweetener, can sustainably replace refined sugar and enhance the nutritional profile of snack products.
Keywords: Date Fruit; Deep frying; Snack; Snacking Doughnut; Sugar; Wheat Flour